The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2166/wst.2022.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing membrane aerated biofilm reactor configurations in mainstream anammox applications

Abstract: Partial nitritation anammox (PNA) membrane aerated biofilm reactors (MABR) have the potential to be employed in mainstream wastewater treatment and can drastically decrease the energy and carbon requirements for nitrogen removal. Previous PNA MABR studies have looked at 1-stage systems, but no study has holistically compared the performance of different MABR configurations. In this study, a PNA MABR was mechanistically modelled to determine the impact of the reactor configuration (1-stage, hybrid, or 2-stage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…14 Many studies have shown that biofilm technologies work well for shortcut nitrogen removal processes, but that there is still room for improvement, particularly with respect to enhancing the colonization and retention of anammox biomass. 10,13,[15][16][17] Because of their ability to sorb and therefore concentrate ammonium, zeolite-coated membranes and biofilm carriers could improve current biofilm technologies for shortcut nitrogen removal by enriching the local environment for ammonium. 18,19 It is thought that if ammonium is present at a higher concentration, it could improve both the rate at which anammox bacteria colonize solid supports and their retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Many studies have shown that biofilm technologies work well for shortcut nitrogen removal processes, but that there is still room for improvement, particularly with respect to enhancing the colonization and retention of anammox biomass. 10,13,[15][16][17] Because of their ability to sorb and therefore concentrate ammonium, zeolite-coated membranes and biofilm carriers could improve current biofilm technologies for shortcut nitrogen removal by enriching the local environment for ammonium. 18,19 It is thought that if ammonium is present at a higher concentration, it could improve both the rate at which anammox bacteria colonize solid supports and their retention.…”
Section: Introductionmentioning
confidence: 99%
“…14 Many studies have shown that biofilm technologies work well for shortcut nitrogen removal processes, but that there is still room for improvement, particularly with respect to enhancing the colonization and retention of anammox biomass. 10,13,15–17…”
Section: Introductionmentioning
confidence: 99%
“…Não há registro de estudos experimentais utilizando o MABR no póstratamento de reatores UASB, com a maior parte dos estudos avaliando-o para tratamento de efluentes sintéticos (WAGNER et al, 2022). Para efeito de comparação, Bunse et al (2020), aplicando o MABR para tratamento de esgoto doméstico bruto (sem remoção prévia de matéria orgânica), obteve resultados ligeiramente piores: 40% de remoção de NT operando um reator com taxa de aplicação superficial de N de 2,0 g N/m 2 /dia e TDH médio de 15,8 h. Por outro lado, Augusto et al (2018), operando um MABR em escala de bancada para um efluente sintético com concentração de nitrogênio amoniacal 50 mg N/L e sem carbono orgânico, obteve remoção média NT de 78% para um TDH de 24h (taxa de aplicação de nitrogênio por área de membrana não reportada).…”
Section: Concentrações Efluentesunclassified